Scientific articles of nursing: analysis of the ethical dimensions - Rosiléa Alves Nogueira; Wilma Dias Fontes; Maria de Nazaré de Oliveira Fraga; Marta Maria Coelho Damasceno (Rev Rene)
This study had the objective of discovering as it is evidenced the ethical aspects in researches involving human beings. It was developed starting from the analysis of 69 scientific articles of nursing, involving human being, had published by the Brazilian Magazine of Nursing – REBEn, during the period from 1994 to 1998. The data evidence that were absent in the research reports the references on: the free and illustrious consent (98,6%); the protection to vulnerable groups (58%); the charity 40,6%); the non harmfulness (60,9%); and the justice and justness (94,2% and 98,6%, respectively). In conclusion, the analyze the research reports allows to infer a wide spectrum of situations, that can show the ignorance of the Resolution that treats of the guidelines for the accomplishment of researches with human beings, a sub-valorization of this focus for the scientific community, until an extreme evidence of the absence of such beginnings. Due to this reality, they suggest that the all the people involved in the production and publication of the nursing researches, the observance and the demand of the respect to referred them ethical dimensions, that will take the adoption of new attitudes front to the care, permeated by commitment, justness and respect.